Flexural Behavior of Reinforced Concrete Beams using Recycled Glass as a Sand Substitute - Lam, T. Q. K.; Ho, H. E. (Engineering, Technology & Applied Science Research, 2025)
Construction waste, representing a major part of the total solid waste generated in urban areas, contains glass and recycling this glass can partially replace sand as aggregate in concrete. This study experimentally investigates the flexural behavior of 7 Reinforced Concrete (RC) beams, utilizing Recycled Glass (RG) as fine aggregate to substitute 0%, 10%, 50%, and 100% of the sand component’s weight in the concrete mix. The study identified the load at which the beams cracking initiated, the progression of the cracks, and the subsequent damage. It established relationships between load and Vertical Displacement (VD), as well as load and deformation in the Tension Zone (TZ) and Compression Zone (CZ) at the mid-span of the RC beam using a 4-point bending test. The research findings indicate that a 10% RG content can effectively substitute sand in concrete beams, with stirrups measuring 125 mm at the ends of the beam and 100 mm at the midpoint of the beam span.